Fifth Five Year Plan (1974-79) Proposals For Annual Plan 1975—76 (Volume I) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1974)
Andaman and Nicobar Islands consist of 319 islands, of which only 38 islands are inhabited at present. . The colonization of major uninhabited islands such as Little Andaman’s, Great Nicobar and Katchal is already in hand under the Special Areas Development Programme. The population for Andaman and Nicobar Islands was 1,15,133 according to' 1971 Census, which has increased at present to about 1,45,000.- The question of formation of a Forest Corporation for gearing up our timber resources is actively being pursued by this Administration. To belie with, an allotment of Rs. 4 crores has been approved by the Planning Commission as State Share Capital, of Equity for the Formation of this Forest Corporation. The Andaman and Nicobar Islands constituted a single District Territory until recently, but the Territory has been bifurcated into two Districts, namely, the Andaman’s District and the Nicobars District as of 15th August this year.
Andaman and Nicobar Administration
Andaman and Nicobar Administration
Keywords: Andaman and Nicobar Islands; Fifth five year plan 1974-79; Proposal for the annual plan for 1975-76; Resources position; Sectoral Review; Minimum Needs Programme; Programme for backward areas/Communities/Hill Tribal areas; Mutual Calamities; Administrative Policy; Institutional frame work; Crop Husbandry